The ways of expressing metaphors of space, time and life in English and Uzbek Media Texts - Yuldosheva, Shafoat Yuldosh qizi (The Lingua Spectrum, 2026)
This article is devoted to the comparative study of the ways of expressing metaphors of space, time and life in English and Uzbek media texts. In modern linguistics, metaphor is considered not only as a stylistic device, but also as an important cognitive mechanism through which human beings conceptualize abstract phenomena, social processes and cultural values. From this point of view, media texts are of particular importance, because they actively influence public consciousness, shape social attitudes and reflect the linguistic worldview of a particular nation. The article analyzes how the concepts of space, time and life are represented through metaphorical expressions in English and Uzbek journalistic discourse. In media language, space is often associated with movement, direction, boundary, distance, expansion and social position. Time is metaphorically expressed through images of flow, path, pressure, change, speed and historical continuity. Life, in turn, is conceptualized as a journey, struggle, development, test, stage or process of transformation. These metaphorical models help journalists present complex political, economic, social and cultural events in a more vivid and understandable form.